More powerful cluster randomized control trials - Brendon McConnell; Marcos Vera-Hernández (Institute for Fiscal Studies (IFS), 2022)
Balanced experimental designs, in which the number of treatment and control units are the same, do not maximize power subject to a cost constraint when treat-ment units are more expensive than control ones. Despite this, such balanced designs are the norm in economics. This paper describes methods to optimally choose the number of treatment and control clusters, and the number of units within treatment and control clusters, allowing for full flexibility. We use three archetypal examples from the development literature to illustrate the magnitude of the power gains, which lie between 8.5 and 19 percentage points.
Keywords: C8; C9; 330; Power analysis; Sample size calculations; Randomized Control Trials; Cluster Randomized Control Trials